Investigation of the process of separation of hard-to-divide weeds from seed mixtures of perennial grasses - Kovalyshyn Stepan; Dadak Viktor (BIO Web of Conferences, 2018)
The work is devoted to the study of seed separation process of perennial grasses on a pneumatic-electric separator. It highlights the main problems of their post-harvest treatment. The influence of the regulated parameters - the magnitude of the supply of seeds to the air-separator, the air flow rate and the electric field strength on the quality from the segregated seed material of the perennial rye-grass were determined by conducting a multifactorial experiment. The optimal values of the regulated parameters of the pneumatic electric separation are substantiated, in which the content of heavy separating admixture of weeds in the seed mixture of perennial rye-grass is the least. It is proved that the use in the technological line of seed preparation of perennial grasses of the pneumatic electric separator allows to ensure the quality of the seed material of the perennial rye-grass in accordance with the requirements of the existing standards.